Expression of Focal Adhesion Kinase in Patients With Endometrial Cancer: A Clinicopathologic Study. Issue 7 (1st October 2009) - Gabriel, Boris; Hasenburg, Annette; Waizenegger, Miriam; Orlowska-Volk, Marzenna; Stickeler, Elmar; Zur Hausen, Axel
Abstract : Introduction: The pp125 focal adhesion kinase (FAK) plays a pivotal role in tumor cell signaling. Focal adhesion kinase expression has been linked to tumor cell proliferation, invasion, and metastasis, but data on endometrial cancer are inconclusive. Methods: We assess FAK expression by immunohistochemistry in endometrial cancer for its value to predict patient prognosis. Results: Of 134 endometrial cancer cases, 120 (89%) revealed moderate and strong expressions of FAK, whereas weak expression was found in 14 (11%) tumors. Kaplan-Meier analysis indicated a clear trend toward improved survival rates for patients with endometrial carcinomas weakly expressing FAK, and notably, there was neither lymph node metastasis nor tumor-related death in this patient subgroup. Increased expression of FAK correlated with higher histological tumor grade ( P = 0.002), lymphatic vascular space invasion ( P = 0.003), and vascular space invasion ( P = 0.02). Significant prognostic survival variables were tumor stage ( P < 0.01), histological type ( P < 0.01), tumor grade ( P = 0.028), and pelvic lymph node status ( P = 0.035). Multivariate Cox regression analysis identified histological tumor grade as a significant independent predictor of patient survival (hazards ratio, 2.71; P = 0.03). Conclusions: Further studies are warranted to elucidate whether FAK expression analysis is a suitable tool in stratifying patients at different risks of disease progress, and wether FAK might become a new molecular target for endometrial anticancer therapy.